FHL2 switches MITF from activator to repressor of Erbin expression during cardiac hypertrophy. (15th September 2015) - Rachmin, Inbal; Amsalem, Eden; Golomb, Eliahu; Beeri, Ronen; Gilon, Dan; Fang, Pengfei; Nechushtan, Hovav; Kay, Gillian; Guo, Min; Yiqing, Peter Li; Foo, Roger S.-Y.; Fisher, David E.; et al.
Abstract: Background: Congestive heart failure (CHF) is a significant health care burden in developed countries. However, the molecular events leading from cardiac hypertrophy to CHF are unclear and preventive therapeutic approaches are limited. We have previously described that microphthalmia-associated transcription factor (MITF) is a key regulator of cardiac hypertrophy, but its cardiac targets are still uncharacterized. Methods and results: Gene array analysis of hearts from MITF-mutated mice indicated that ErbB2 interacting protein (Erbin) is a candidate target gene for MITF. We have recently demonstrated that Erbin is decreased in human heart failure and plays a role as a negative modulator of pathological cardiac hypertrophy. Here we show that Erbin expression is regulated by MITF. Under basal conditions MITF activates Erbin expression by direct binding to its promoter. However, under β-adrenergic stimulation Erbin expression is decreased only in wild type mice, but not in MITF-mutated mice. Yeast two-hybrid screening, using MITF as bait, identified an interaction with the cardiac-predominant four-and-a-half LIM domain protein 2 (FHL2), which was confirmed by co-immunoprecipitation in both mouse and human hearts. Upon β-adrenergic stimulation, FHL2 and MITF bind Erbin promoter as a complex and repress MITF-directed Erbin expression. Overexpression of FHL2 alone had no effect on Erbin expression, but in the presence of MITF, Erbin expression was decreased. FHL2–MITF association was also increased in biopsies of heart failure patients. Conclusion: MITF unexpectedly regulates both the activation and the repression of Erbin expression. This ligand mediated fine tuning of its gene expression could be an important mechanism in the process of cardiac hypertrophy and heart failure. Graphical abstract: Highlights: We demonstrated in vivo and in vitro that MITF regulates Erbin expression in the heart. Under normal conditions MITF activates cardiac Erbin expression. MITF represses Erbin expression during cardiac hypertrophy. MITF associates with FHL2 and mediates Erbin repression as a complex. MITF and FHL2 association is increased in heart failure patients.